Access Control Secure to Restricted Information Resources for IEEE 802.11 Wireless Networks - Mejía-Nogales, J.L.; Vidal-Beltrán, S.; López-Bonilla, J. (Kathmandu University Journal of Science, Engineering and Technology, 2009)
Information security has been one of the most sensible issues when designing communications systems; especially when this information is cataloged as confidential. The present document deals with a secure system that let you get access to privileged data, when the medium access is a wireless network based on IEEE 802.11 standards.The system designed is conformed by three main functions, which capture the first http request and forward it to an authentication server; the server validates the user’s identity in order to give access to the information resources. The control access entity determines which users are allowed or denied from the system. These functions are performed by a Captive Portal, an authentication Server and an Access Point.